The Influence of Intellectual Intelligence and Learning Motivation Against Student’s Mathematics Learning Outcomes In Region 3 Kelurahan Pegadungan Jakarta Barat - Handarini, Dwi Ningrum (Syntax Literate, 2021)
This study aims to prove the influence of intellectual intelligence and learning motivation on students' math learning results partially or simultaneously. Defenisi learning results in this study is the acquisition of the student's learning process in accordance with the objectives of teaching in the cognitive sphere covering aspects of C1 (remember), C2 (understand), and C3 (applying). Intellectual intelligence or IQ is often referred to as intelligence that refers to a person's cognitive abilities, namely high thinking ability in an effort to improve a student's abilities, the ability to reason to plan problems, understand ideas, use language and learn. Learning motivation is a mental drive or strength that encourages, moves, and directs students to learn. This research uses quantitative approach with survey method. The sampling technique uses propotional random sampling techniques. The sample of this study was grade 6 students with a total of 92 students. Instruments used in the form of IQ test data, questionnaires and tests. Data analysis using multiple linear regression regression. The results showed that (1) Intellectual intelligence has a significant influence on students' math learning outcomes, (2) learning motivation has a significant influence on students' math learning outcomes, (3) Intellectual intelligence and learning motivation have a significant influence on students' math learning outcomes. The results of this study can be used as a reference for schools that want to get maximum student math learning results.